Consumer knowledge, attitude and practices towards lead contamination Part 1: Street-vended fishballs - Garcia, Sheryl Gomez; Dumelod, Benelyn Domingo (2003)
ABSTRACT Lead poisoning continues to be a major health problem in the world. It is for this reason that lead holds a prominent place in the food laws of most countries. It is probably the metal which has had more official consideration and about which more has been written than any other inorganic contaminant of food and environment. The objective of this study is to determine consumer knowledge, attitude and practices in relation to lead contamination in foods and utilize street-vended fishballs sold along selected polluted areas within Quezon City, as a representative in the subsequent analysis for lead using Flame Atomic Absorption Spectroscopy. The study is divided into three phases. Phase 1 dealt with a survey on the consumers' awareness, attitude, and practices in relation to lead contamination. In Phase 2, the uptake and retention of lead in fishballs were characterized. The lead content of raw fishballs rose from < 0.1 mg/kg to 0.18 mg/kg after 30-minute direct exposure to the exhaust fumes of a car loaded with leaded gasoline. Frying of the raw, exhaust-exposed fishballs for 0.5, 1.0 and 1.5 minutes at 150°C did not effect any change in the level of lead. In Phase 3, the lead contents of four lots of street-vended fishballs variably exposed to exhaust fumes from passing and idling vehicles were evaluated. The fishball samples exhibited lead contents of < 0.5 mg/kg (a level less than the detection limit of the method).
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Snack food -- Analysis; Consumer behavior -- Philippines; Lead -- Toxicology